«Диван Лугат ат-Турк» Махмуда Кашгари как источник изучения материальной культуры тюркских народов - Садыглы, Периназ (Народна творчість та етнологія, 2014)
Знаменитый труд «Диван Лугат атТурк» великого тюркского ученого Махмуда Кашгари, написанный в 1072–1074 годах, является ценным первоисточником для изучения материальной и духовной культуры тюркских народов. В данной статье труд М. Кашгари рассмотрен с точки зрения его значения как историко-этнографического источника. The work Divanü Lüğat-it-Türk by the great Turkish scientist Mahmud Kashgari was written in 1072–1074. It is a valuable primary source for the study of the Turkic material and spiritual culture. In this article, were mainly investigated Turkic people economy activities, learned their features, and made some generalizations in this case.